Improving Freshmen Studentsâ Sentence Accuracy Through Sentence Combining Drills: a Case Study in Bina Nusantara University - Luke, Joice Yulinda; Oktriono, Kristianus (Sebelas Maret University, 2016)
Expressing ideas using accurate sentences is commonly a problematic case for freshmen students due to lack ofÂ sentence structure knowledge and inadequate drillings inÂ classroom. It happens because a lot of freshmen students still produce meaningless and unclear sentences in writings. This phenomenon applies to freshmen students of Bina Nusantara University (BINUS), who took English subject in the first semester. Thus, this study attempts toÂ investigate whether Sentence Combining Drills can improve sentence accuracy ofÂ BINUSÂ freshmen students whoÂ took English Access. For data collection, the study gathered the data fromÂ forty eightÂ freshmen students who shareÂ similarity inÂ upper-intermediateÂ level of English. The research method will scrutinize the results from the studentsâÂ scores and studentsâ opinions about positive improvements as written in the questionnaires. The study used descriptive qualitative analysis to discuss the findings. The findings of the research proved that practicing sentence combining exercises can boost the scores of sentence constructions and improves the quality of studentsâ writing. At the same time, the results of the study are valuable for enriching approachesÂ ofÂ teaching academic writing inÂ EFL contexts.